Docking Sulochrin and Its Derivative as α-Glucosidase Inhibitors of Saccharomyces cerevisiae - Wening Lestari; Rizna Triana Dewi; Leonardus Broto Sugeng Kardono; Arry Yanuar (Indonesian Journal of Chemistry, 2017)
Sulochrin is known to have an activity as inhibitors of the α-glucosidase enzyme. In this report interaction of sulochrin to the active site of the α-glucosidase enzyme from Saccharomyces cerevisiae was studied by docking method. The crystal structure of α-glucosidase from S. cerevisiae obtained from the homology method using α-glucosidase from S. cerevisiae (Swiss-Prot code P53341) as a target and crystal structure of isomaltase from S. cerevisiae (PDB code 3A4A) as a template. These studies show that sulochrin and sulochrin-I could be bound in the active site of α-glucosidase from S. cerevisiae through the formation of hydrogen bonds with Arg213, Asp215, Glu277, Asp352. Sulochrin-I has stability and inhibition of the α-glucosidase enzyme better than sulochrin. The iodine atom in the structure of sulochrin can increase the activity as an inhibitor of the α-glucosidase enzyme.